Developing Modern Pain Therapies - Manion, John; Waller, Matthew A.; Clark, Teleri; Massingham, Joshua N.; Neely, G. Gregory (Frontiers in Neuroscience, 2019)
Chronic pain afflicts as much as 50% of the population at any given time but our methods to address pain remain limited, ineffective and addictive. In order to develop new therapies an understanding of the mechanisms of painful sensitization is essential. We discuss here recent progress in the understanding of mechanisms underlying pain, and how these mechanisms are being targeted to produce modern, specific therapies for pain. Finally, we make recommendations for the next generation of targeted, effective, and safe pain therapies.